Sejarah dan dialog peradaban : persembahan 70 tahun Prof. Dr. Taufik Abdullah - Lembaga Ilmu Pengetahuan Indonesia (Menteng, Jakarta : Lembaga Ilmu Pengetahuan Indonesia (LIPI Press), 2005)
Dynamics of the Indonesian history then and present time; festschrift in honor of Taufik Abdullah, an historian, social scientist, and a prominent figure in Indonesian literature
Includes bibliographical references
In Indonesian, with some articles in English
Keywords: Abdullah, Taufik, -- 1936-; Indonesia -- History; Indonesia -- Historiography; Indonesia -- Civilization